A new adapisoriculid mammal (Eutheria) from the early-middle Eocene of Namibia - Goin, Francisco Javier (2022)
Adapisoriculidae, a family of primitive eutherian, insectivore-like small mammals, is known from Europe, mainland Asia, India and Africa (Morocco, Namibia) but not thus far from the New World. Previous discoveries of this family in Africa were restricted to Morocco, but in 2019 a specimen was found in early to middle Eocene freshwater limestones at Black Crow, Namibia, thereby greatly extending the geographic range of the family well to the south of all other records of the group, even taking into account the northward drift of India since the early Palaeogene. A new genus and species is described and compared in detail with other members of the family as well as with other small-bodied eutherians and placentals. Its biogeography is discussed, but the limited amount of evidence available, allied with the huge geographic and temporal gaps in its distribution, does not yield a clear picture of where the family originated and when it dispersed to other parts of the Old World.